Jonne Kähkönen speaks about his coaching philosophy - Sattlecker, G. (Journal of Biathlon Coaching, 2025)
In this interview, Jonne Kähkönen discusses his coaching philosophy with the Italian biathlon team, emphasizing the balance between training intensity, recovery, and mental health. He highlights the importance of adapting training programs to individual needs while fostering teamwork. Kähkönen reflects on a key highlight of the recent training season, the early snow camp in Vuokatti, and outlines his plans for future Olympic preparations. He also shares insights on injury prevention, team dynamics, and maintaining mental toughness, stressing the significance of communication and team cohesion for success in high-performance sports.